Neuroprotective effects of Nigella Sativa seeds and Murraya Koenigii Leaves extracts in a two vessel occlusion rat model of Azheimer's disease - Azzubaidi, Marwan Saad Abdulrahman (Kulliyyah of Medicine, International Islamic University Malaysia, 2012)
Nigella sativa seeds oil (NSO) and Murraya koenigii leaves (MKL) demonstrated robust antioxidant and anti-inflammatory activities in vitro and in vivo. Two vessel occlusion surgery (2VO) is an established rat model of Alzheimer's disease (AD) which causes chronic cerebral hypoperfusion resulting in oxidative stress and neuroinflammation. These events lead to neurodegenerative brain changes especially within CA1 region of the hippocampus where spatial memory neurons are situated. This experimental intervention study was designed to assess the potential neuroprotective effect of the two herbal plants extracts when given orally to experimental animals ten days before 2VO surgery and continued until the tenth week post 2VO. The assessment was based on cognitive, histopathological and electron microscopical brain tissue analyses. 80 rats were equally divided into 4 main groups namely sham control, 2VO, NSO+2VO and MKL+2VO groups. Each one of them was further subdivided according to the experimental protocol of Morris water maze (MWM) test into long-term memory (LTM) subgroups which underwent acquisition MWM trials before 2VO and were retested for LTM performance on the 10th postoperative week, while the other subgroups were only introduced to MWM during the 10th postoperative week. These subgroups were tested by short-term memory (STM) and working memory test (WMT) protocols in a row. 2VO induced significant LTM, STM and learning impairment in 2VO rat group as compared to sham control as well as NSO+2VO groups, whereas the attenuation of 2VO induced memory impairment achieved by MKL treatment was significantly lower than that of sham control and NSO+2VO groups. The brain tissue analyses included histopathological as well as Transmission Electron Microscopy (TEM) examinations. Light microscope histopathology revealed significantly higher number of viable hippocampal cells in sham control and NSO treated rats groups as compared to untreated 2VO and MKL treated groups. Simultaneously, ultrastructural neurodegenerative changes were observed in CA1 hippocampal subfield of 2VO group which comprised necrosis and apoptosis of pyramidal neurons, astrocytic degeneration with microgliosis and thickening of endothelial basement membranes of hippocampal capillaries. These changes were substantially less demarcated in NSO treated group and were almost completely absent in sham control group. However, a great deal of similarity in ultrastructural deformities was found between untreated 2VO and MKL+2VO groups. It can be concluded that NSO, by virtue of its antioxidant and anti-inflammatory activity, was capable of preventing hippocampal neurodegeneration induced by 2VO, while MKL extract was only able to exert a modest preservation of memory without a neuroprotective effect on CA1 hippocampal neurons after cerebrovascular hypoperfusion initiated by 2VO surgery.